2009
DOI: 10.1007/s00213-009-1677-2
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of hypnotic drugs in aging drivers submitted to simulated accident scenarios: an exploratory study

Abstract: This study did not reveal any major residual effects of the hypnotics studied on driving performance in aging drivers. However, the urban driving situations used here for the first time in the evaluation of drugs revealed some modifications in driving habits which could lead to risky behavior. It thus appears that urban driving simulations are useful for gaining knowledge about the effects of drugs on driving behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…Nevertheless, two types of data published in recent years are in accord with the present results and indicate that Zp could lead to risks. We found that in urban driving tests with accident scenarios, Zp tends to produce more risky behaviour compared to placebo (Meskali et al 2009). Moreover, a pharmaco-epidemiological study exploring the risk of accidents associated with Zp use reported a twofold increase in risk with this drug (and also with Zc) during the first week after filling a prescription (Gustavsen et al 2008).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, two types of data published in recent years are in accord with the present results and indicate that Zp could lead to risks. We found that in urban driving tests with accident scenarios, Zp tends to produce more risky behaviour compared to placebo (Meskali et al 2009). Moreover, a pharmaco-epidemiological study exploring the risk of accidents associated with Zp use reported a twofold increase in risk with this drug (and also with Zc) during the first week after filling a prescription (Gustavsen et al 2008).…”
Section: Discussionmentioning
confidence: 91%
“…The driving simulator has previously been described (Meskali et al 2009). The driving test involved driving for 60 min during the day along a motorway in monotonous conditions (no traffic, repetitive landscape).…”
Section: Driving Simulator Testmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, zolpidem use was associated with an inconsistent rate of speed, an increased number of lane departures in monotonous driving environment simulations and a modified lateral vehicle position in urban driving situations with accident scenarios. (Meskali et al 2009, Bocca et al 2011) Furthermore, it was not surprising that the strongest associations in the current study were among females and participants aged ≥ 80 years. Older adults and women have lower clearance rates and higher plasma concentrations for a given zolpidem dose compared to younger adults and men, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…The effect of learning the driving circuits and foreseeing the events may have resulted in improved driving performances (e.g., better crash avoidance) over the course of the four drives, in which case the effects of alcohol would have been attenuated. Urban events thus may not be regarded as completely unexpected, probably increasing the participants' alertness which in turn could have improved their driving performance (Meskali et al 2009). Thus, they were probably unable to induce a real-life reaction unlike for the highway scenario, which has been proved to involve behaviors that are relatively similar to those of natural driving.…”
Section: Discussionmentioning
confidence: 99%